Effect of the addition of wheat fiber and partial pork back fat on the chemical composition, texture and sensory property of low-fat bologna sausage containing inulin and oat fiber - Silva Barretto, Andrea Carla da [UNESP]; Bertoldo Pacheco, Maria Teresa; Rodrigues Pollonio, Marise Aparecida (Soc Brasileira Ciencia Tecnologia Alimentos, 2015)
The objective of this work was to study the effect of adding wheat fiber and partial pork back fat on the quality characteristics of bologna sausage. The compound central rotating design was used with treatments containing fixed levels of inulin (5%) and oat fiber (1%) and variable levels of wheat fiber (0-4%) and pork back fat (0-10%). The pH and protein were similar in all the treatments, the fat was lower than the control treatment and the moisture content was higher than the control treatment (CF) without fibers. The wheat fiber increased the hardness and reduced cohesiveness and scores were given for overall impression. We found that it was possible to prepare low-fat bologna sausage with the addition of 6.58% fiber (5% inulin, 1% oat fiber and 0.58% wheat fiber), whilst retaining good sensory acceptability, thus reducing the pork back fat levels by between 25 and 42.75%.
Keywords: Fat substitutes; Wheat fiber; Bologna sausage; Microstructure